Analysis of monitoring parameters of wear of rolling stock wheel pairs (Transport systems and technologies, 2019)
The article analyzes the systems of control of the technical condition of wheel pairs both on the railways of Ukraine and in the world. The advantages and disadvantages of these systems, especially their use and operation are revealed. The principle of operation and components of systems, through which the fixation and control of parameters of wear of wheel pairs is carried out, is considered. After analyzing the existing systems of checking the technical condition of wheel pairs, the experience of their use, the advantages and disadvantages of different systems and devices, the authors have proposed a stationary device for controlling the technical condition of the wheel pairs of rolling stock of railways, based on the automatic control of the technical condition of the wheel pairs of the rolling stock when moving from stationary installation installed on a rail track and connected to automated rolling stock systems. Taking into account the analysis of the investigated material, conclusions were made on the feasibility of introducing a fully-fledged automated control of the technical condition of the wheel pairs, the prospects of using these systems on the railways of Ukraine.
Keywords: rolling stock of railways, wheel pair, rolling surface, monitoring system, control of wear parameters